Stories in social-ecological knowledge cocreation - Diego Galafassi; Tim M. Daw; Matilda Thyresson; Sergio Rosendo; Tomas Chaigneau; Salomão Bandeira; Lydiah Munyi; Ida Gabrielsson; Katrina Brown (Ecology and Society, 2018)
Transformations in social-ecological systems to overturn poverty and ecosystem degradation require approaches to knowledge synthesis that are inclusive and open to creative innovation. We draw on interviews with participants and in-depth process observation of an iterative knowledge cocreation process in Kenya and Mozambique that brought together scientists, community representatives, government representatives, and practitioners who had expertise or experience in poverty and/or coastal natural resource use and management. We analyze the communicative spaces opened by techniques of system diagrams and future scenarios, and provide a rich account of the emergent process of developing a "shared conceptual repertoire" as a basis for effective communication and knowledge synthesis. Our results highlight the difficulties of challenging dominant narratives and the creative potential that exists in reflecting on their underpinning assumptions. In our analysis, stories and lived experiences emerged as key means shaping the construction of shared concepts and ideas. We conclude by outlining the implications of designing knowledge cocreation processes that support the task of devising systemic interventions that are robust for a range of future scenarios. This includes embracing the role of stories in generating shared meanings and opening up spaces for exploration of knowledge assumptions that are embedded in intervention narratives.